Optimal Strategies for the Management of Macromastia and Breast Ptosis for Patients Undergoing Nipple-sparing Mastectomy - Moreira, Andrea A.; Kozorosky, Erica; Coopey, Suzanne B. (Journal of Reconstructive Microsurgery, 2025)
High-volume breasts pose challenges for nipple-sparing mastectomy (NSM) due to their large size, indistinct tissue boundaries, and high degree of ptosis. Historically, NSM was not considered feasible for such cases, but advancements in surgical techniques have expanded eligibility criteria.We developed a surgical algorithm for patients with macromastia and ptosis undergoing NSM. We also outline techniques for preserving the nipple–areolar complex (NAC) based on the severity of macromastia and breast ptosis, especially when immediate mastopexy/reduction is required during mastectomy. The proposed algorithm provides a practical guide for surgeons managing these complex cases.By employing carefully selected approaches, it is possible to successfully preserve the NAC in high-volume breasts undergoing NSM. This broader eligibility criteria not only accommodates a more diverse patient population but also enhances their quality of life and improves aesthetic outcomes.Advancements in surgical techniques have made NSM a viable option for breast reconstruction in high-volume breasts. By addressing challenges and preserving the NAC through carefully selected approaches, surgeons can improve outcomes and quality of life for patients undergoing NSM.
Keywords: breast reconstruction; implant-based breast reconstruction; breast reconstruction in large and ptotic breasts